Validity of the disabilities of the Arm, Shoulder and Hand patient-reported outcome measure (DASH) and the Quickdash when used in Dupuytren’s disease - Rodrigues, J.N.; Zhang, Weiya; Scammell, Brigitte E.; Russell, P.; Chakrabarti, I.; Fullilove, S.; Davidson, D.; Davis, T. (SAGE, 2016)
This study investigated aspects of the validity and reliability of the 30-item Disabilities of the Arm, Shoulder and Hand patient-reported outcome measure (DASH) and its relationship with the shorter 11-item QuickDASH in patients with Dupuytren’s disease. Seven hundred and fifty-nine DASH questionnaires were studied, covering pre- and postoperative patients undergoing different treatments for Dupuytren’s disease. Items related to pain rose early after treatment before returning to baseline, suggesting that studying pain is relevant during postoperative recovery. Across all 759 sets of responses, the QuickDASH agreed closely with the DASH. In exploratory factor analysis, the DASH was not unidimensional, questioning the validity of the DASH summary score in Dupuytren’s disease. Further validation of existing PROMs for use in Dupuytren’s disease is needed. These data suggest that pain is a relevant symptom to study during postoperative recovery following treatment for Dupuytren’s disease.